2017
DOI: 10.3389/fpls.2017.01120
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Analysis of Genes, Conserved between japonica and indica Rice Cultivars, that Respond to Low-Temperature Stress at the Vegetative Growth Stage

Abstract: Cold stress is very detrimental to crop production. However, only a few genes in rice have been identified with known functions related to cold tolerance. To meet this agronomic challenge more effectively, researchers must take global approaches to select useful candidate genes and find the major regulatory factors. We used five Gene expression omnibus series data series of Affymetrix array data, produced with cold stress-treated samples from the NCBI Gene Expression Omnibus (http://www.ncbi.nlm.nih.gov/geo/),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 145 publications
(134 reference statements)
2
21
0
Order By: Relevance
“…WRKY transcription factors are also considered as master regulators of molecular reprogramming to enhance the stress tolerance of plants [51]. Transcription factor WRKY71 has been shown to help evade salt stress in Arabidopsis and enhance cold tolerance in rice [52,53]. DEG analysis revealed that OsWRKY71 showed upregulation (6.00-fold) in OsEXPA7-OX plants under salt stress ( Figure 10E), which was confirmed by qRT-PCR results.…”
Section: Genes Involved In Salt Stress Tolerance Were Significantly Amentioning
confidence: 53%
“…WRKY transcription factors are also considered as master regulators of molecular reprogramming to enhance the stress tolerance of plants [51]. Transcription factor WRKY71 has been shown to help evade salt stress in Arabidopsis and enhance cold tolerance in rice [52,53]. DEG analysis revealed that OsWRKY71 showed upregulation (6.00-fold) in OsEXPA7-OX plants under salt stress ( Figure 10E), which was confirmed by qRT-PCR results.…”
Section: Genes Involved In Salt Stress Tolerance Were Significantly Amentioning
confidence: 53%
“…Based on GO analysis, CaChi genes imply a role in different stresses, in support of our study. Kumar et al (2017) [65] also investigated the OsWRKY71 gene enhanced cold tolerance and mainly involved in metabolic as well as in regulatory pathways in rice, while Eroglu and Aksoy (2017) [66] studied COP9 response under Fe deficiency in Arabidopsis. Hence, we extended our study to investigate the expression analysis of eight representative CaChi after salt (NaCl), cold (6 °C) and drought (mannitol) stresses (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…In plants, abiotic stress positively triggers the levels of ABA and reactive oxygen species (ROS) [75] such as H 2 O 2 [76][77][78][79]. High H 2 O 2 levels trigger cytosolic calcium concentration via nitric oxide (NO) [80,81].…”
Section: Calcium Signaling Integration With Aba Signaling Pathway Andmentioning
confidence: 99%